Object drop in imperatives and the status of imperative subjects. - Bošković, Željko (Journal of Slavic Linguistics)
The paper examines object drop in imperatives and argues that the null object in question undergoes movement to the left periphery. The paper also examines the position of overt imperative subjects, and argues that in some, but not all languages overt imperative subjects undergo movement to the left periphery, where the crosslinguistic variation in question correlates with the precise verbal form used in imperatives, the relevant difference being true imperatives vs other/bare forms used as imperatives (the latter leads to movement of overt imperative subjects to the left periphery).